Effect of Shooting Exercise On Accuracy Of Football Penalties - Dedi Nurwiyandi (Journal of Physical Education and Sport Science, 2019)
The effect of straight-forward step shooting practice and sideways prefix on the accuracy of penalty kicks on soccer extracurricular members in Junior High School, Health and Recreation Physical Education Study Program, 2015, 103 pages. This research is motivated by the level of accuracy or accuracy of student kicks in soccer games is still low. This is evidenced by students shooting or kicking not in accordance with the target or target, the kick out and the direction is not certain. This is evidenced from the results of the accuracy of the penalty kick test with the lowest score of 7, the highest score of 15 and obtaining an average of 10.133 including the category still low with interval distance 5 - 11. The purpose of this study is to compare data on the results of the initial step shooting exercise straight with a sideways prefix on the accuracy of penalty kicks on soccer extracurricular members in junior high. The population in this study were 30 students participating in soccer extracurricular activities in junior high school. The sampling technique used was total sampling by determining the population to be used as research samples so that students from the extracurricular football teams in junior high school were numbered 30 students. The data collection technique used is the test of shooting the ball to the target (shooting). The data analysis technique in this study is the normality test and hypothesis test (t test) which is used to compare data from the effect of the prefix straight step shooting practice with a sideways prefix on the accuracy of penalty kicks on soccer extracurricular members in junior high school. Based on the results of statistical testing with t test obtained t hit (14,669)> t daf (1,70), then accept Hi means that there is a comparison of the effect of the prefix straight step shooting exercise with a sideways prefix on the accuracy of penalty kicks on soccer extracurricular members in junior high. The conclusion of this study is that there is a comparison of the effect of the prefix straight-step shooting practice with the sideways prefix on the accuracy of penalty kicks on soccer extracurricular members in junior high school.